PERILAKU IBU NIFAS MENGKONSUMSI KAPSUL VITAMIN A DI KECAMATAN KOTAPINANG KABUPATEN LABUHANBATU SELATAN - Putra Apriadi Siregar (Universitas Respati Yogyakarta, 2020)
Background: The behavior of postpartum mothers in consuming vitamin A capsules is very important. The postpartum period is a very important period for postpartum mothers and their babies. During the postpartum period, a mother must have sufficient vitamin A to meet the needs of vitamin A for postpartum mothers and babies. Objective: To determine the behavior of postpartum mothers in consuming vitamin A capsules in the Kotapinang District, Labuhan Batu Selatan Regency. Method: cross-sectional research with purposive sampling technique. The study population was all postpartum mothers who were in the working area of Kotapinang District as many as 355 people and the research sample was 57 people. Presentation of data using frequency distribution tables. Results: The predisposing factors for postpartum mothers included the moderate knowledge category, namely 24 people (42.1%), 23 people (40.4%) good attitude category, the enabling factors for most of the health centers/practice of health workers (midwives, doctors). too far from home as many as 43 respondents (75.4%). Reinforcing factors, namely health workers never explain/provide counseling about vitamin A capsules as many as 31 respondents (54.4%), families did not explain consuming vitamin A capsules as many as 46 respondents (80.7%). The action of postpartum mothers in consuming vitamin A capsules was at a deficient level, namely 24 people (42.1%). Conclusion: The action of postpartum mothers in consuming vitamin A capsules was at a deficient level, namely 24 people (42.1%).